DESIGN OF A CATHOLIC RETREAT HOUSE IN WEST JAVA - Angelia Meganingsih, Debora
Growing up amidst the pressures of life puts teens on the verge of a crisis, which can trigger negative character formation. Therefore, Catholic educational foundations implement retrets as a medium for forming the character of teens to become better individuals. Through the retret, teens are guided to find their purpose in life and return to holding on to God in facing life's ups and downs. The design of a retret house for teens is faced with a major problem, specifically how to create a spatial atmosphere that is in sync with the preferences of teens at the time but also capable of directing teens to awareness of patterns of correct behavior. To answer these problems, a concept is needed to overcome the three main characteristics of teens, which are hypocrisy, egoism, and social exclusivism. Based on these characters, a concept was made that aims to bring teens to look outside themselves, towards an awareness of reality. This concept is explained into three keywords: paradoxical, sensibility, connectivity. Paradoxical aims to provide a different point of view in seeing things, a connection between two opposite conditions that influence one another. Sensibility aims to invite a person to see life outside of himself, that he is not struggling alone, and shows how an action has a different impact on other people. Connectivity aims to awaken equality and kinship as a social unit, to provide an understanding of how one's life is essentially inseparable from others, both within and outside the group.